2021
DOI: 10.2147/ijn.s300428
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Gram-Positive and Gram-Negative Bacteria by Zinc Oxide Hedgehog Particles

Abstract: Purpose: Nanomaterials for antimicrobial applications have gained interest in recent years due to the increasing bacteria resistance to conventional antibiotics. Wound sterilization, water treatment and surface decontamination all avail from multifunctional materials that also possess excellent antibacterial properties, eg zinc oxide (ZnO). Here, we assess and compare the effects of synthesized hedgehog-like ZnO structures and commercial ZnO particles with and without mixing on the inactivation of bacteria on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Besides, we noticed distinct aggregation of hemocytes and enhanced phagocytosis in response to ZnO-NP injection. These results were in agreement with previous research conducted in vitro that nano-ZnO films could promote microbial clearance by macrophages and polymorphonuclear leukocytes by facilitating phagocytic efficacy (Rutherford et al, 2021). It has been recently revealed that the phenoloxidase activity of G. mellonella was induced after C. albicans infection (Sheehan and Kavanagh, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Besides, we noticed distinct aggregation of hemocytes and enhanced phagocytosis in response to ZnO-NP injection. These results were in agreement with previous research conducted in vitro that nano-ZnO films could promote microbial clearance by macrophages and polymorphonuclear leukocytes by facilitating phagocytic efficacy (Rutherford et al, 2021). It has been recently revealed that the phenoloxidase activity of G. mellonella was induced after C. albicans infection (Sheehan and Kavanagh, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Gram-negative bacteria have a thin, single-layered peptidoglycan, containing high lipopolysaccharides and an absence of teichoic acid. All these different cell surface compositions result in explicit differences in the sensitivity of bacteria to ZnO nanoflowers [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in good agreement with the reported studies [ 45 , 46 , 47 ]. It is well known that the antibacterial activity of ZnO nanoflowers is dependent on their contents, and that a higher content of ZnO nanoflowers shows higher bactericidal activity owing to their higher surface-to-volume ratios for reacting with bacterium cells [ 42 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown in the antibacterial test results presented in Figures 6 and 7, it has been found that Gram-positive bacteria are less sensitive to ZnHA nanoparticles than Gram-negative bacteria. The reason for this can be attributed to the greater thickness of the peptidoglycan layer in Gram-positive bacteria [67,68] in such a way that the predominant mechanism of inhibiting Gram-positive S. aureus bacteria by ZnHA nanoparticles can be attributed to the induction of downregulating of amino acid synthesis and dysfunction of vital bacterial enzymes [69]. Another mechanism of bacterial inhibition is related to Zn 2+ ions released from the ZnHA-rGO nanosystem into bacteria.…”
Section: Effect Of Zinc On Antibacterial Behaviormentioning
confidence: 99%